PENGARUH CORPORATE GORVERNANCE PRECEPTION INDEX (CGPI), STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - MG. Kentris Indarti; Lusi Extaliyus (Jurnal Bisnis dan Ekonomi, 2013)
This study aimed to examine the influence of Corporate Gorvernance Perception Index (CGPI) , ownership structure , and firm size on financial performance. CGPI is the result of the assessment and ranking of the application of corporategovernance in companies listed on the Indonesia Stock Exchange (IDX) conducted by the Indonesian Institute for Corporate Governance (IICG). The population in this study are listed Company on Corporate Gorvernance PreceptionIndex (CGPI) 2010-2012 . By using purposive sampling obtained a sample of 60 companies . The data analysis technique used is Ordinary Least Square regression (OLS) . The results showed that the variables of Corporate GorvernancePerception Index (CGPI) and managerial ownership effect significant positive on the company's financial performance. Meanwhile, institutional ownership and firm size is not effect significant positive on financial performance.Keywords: good corporate gorvernance, ownership structure, company size and return on equity.